2010
DOI: 10.22358/jafs/66310/2010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of <i>Carnobacterium divergens</i> AS7 bacteriocin on gastrointestinal microflora <i>in vitro</i> and on nutrient retention in broiler chickens

Abstract: The present study was undertaken to evaluate the effects of divercin, a bacteriocin produced by lactobacilli strain Carnobacterium divergens AS7, on the microflora status under in vitro conditions and on nutrient retention and nitrogen-corrected apparent metabolizable energy (AME N ) of divercin in an in vivo trial on broiler chickens. Low (DL) 200 AU•ml 1 (0.05% of the liquid divercin prepatation), and high (DH) 1600 AU•ml -1 (0.4% of the liquid divercin prepatation) doses of divercin were used in both trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
3
9
2
1
Order By: Relevance
“…In the present study, divercin AS7 improved AME n of the diets, whereas the C. perfringens challenge had no effect, partially agreeing with earlier findings also indicating a positive effect of divercin AS7 on AME n values (Józefiak et al, 2010b;Józefiak et al, 2011). However, in the present study, C. perfringens-challenged birds had numerically the lowest AME n value accompanied with the lowest apparent digestibility of crude fat.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, divercin AS7 improved AME n of the diets, whereas the C. perfringens challenge had no effect, partially agreeing with earlier findings also indicating a positive effect of divercin AS7 on AME n values (Józefiak et al, 2010b;Józefiak et al, 2011). However, in the present study, C. perfringens-challenged birds had numerically the lowest AME n value accompanied with the lowest apparent digestibility of crude fat.…”
Section: Discussionsupporting
confidence: 91%
“…Use of the lyophilized divercin preparation was observed to improve performance of the challenged birds, however, not to the same degree as in our previous work (Józefiak et al, 2010b(Józefiak et al, , 2011, where we demonstrated dietary supplementation of divercin AS7 as a liquid preparation to improve broiler performance similar to the use of the ionophore coccidiostat salinomycin.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…at an activity of 800 AU/ml, this bacteriocin does not impair body weight gain or feed conversion and tends to potentially increase AME N contents (P=0.0672; Table 3); however, it also should be pointed out that increasing dietary divercin AS7 levels do not gradually improve the performance results. This observation agrees with our earlier studies which showed that high dosages had better in vitro bacteriostatic effects but did not improve nutrient digestibility in comparison with lower dosages (Józefiak et al, 2010). Moreover results of the present studies may suggest that in vivo divercin AS7 mode of action, is also correlated with GIT microflora composition and/or activity, giving beneficial effects for the host bird when the dietary factors disrupt GIT homeostasis.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in our laboratories have shown that C. divergens AS7 bacteriocin (divercin AS7) may reduce bacterial colonization in vitro and in vivo, potentially improving broiler performance (Józefiak et al, 2010). In the experiments considering the influence of divercin on the broiler GIT microflora and nutrient retention, we used a constant liquid-form dosage of divercin AS7 that was estimated on the basis of in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%